Analisis Nyeri Rhematoid Arthritis Dengan Kemandirian ADL Pada Lansia Di Wilayah Kerja Puskesmas Tungoi - Hairil Akbar; Dalia Novitasari; Riswan Riswan; Eko Budi Santoso (Sekolah Tinggi Ilmu Kesehatan KESDAM IX/Udayana, 2023)
Background: Arthritis, better known as rheumatism, is a disease that attacks the joints and surrounding structures. Society often perceives rheumatism as a trivial disease because it does not cause death, even though if it is not treated immediately, rheumatism can cause abnormal limb function, ranging from lumps, stiff joints, and walking difficulty, to lifelong disability. Based on data from the Tungoi Health Center in 2022 the number of patients affected by rheumatoid arthritis was 127 people which was among the 10 highest number of diseases in the Tungoi Health Center. The study aimed to analyze the relationship between rheumatoid pain and the level of independence of the elderly in the working area of the Tungoi Health Center. Methods: This study used a cross-sectional study approach. The location of the research was the Tungoi Health Center in October 2022. The study population consisted of patients seeking treatment in the working area of Tungoi Health Center with the number of study samples obtained was 92 patients using total sampling. Data analysis was carried out using the chi-square test. Results: the study showed that there was a relationship between rheumatoid pain and the level of independence in the elderly with a value of ? = 0.000. Conclusion: There was a relationship between rheumatoid pain and the level of independence of the elderly in the working area of the Tungoi Health Center. Suggestion: Health workers who are responsible for the Integrated coaching unit (POSBINDU) are to provide support to elderly families so that they participate regularly in the elderly programs provided by the Integrated coaching unit (POSBINDU) and Integrated Healthcare Center (POSYANDU).